Cost-effectiveness of voluntary medical male circumcision for HIV prevention across sub-Saharan Africa: results from five independent models. Issue 2 (February 2023) - Bansi-Matharu, Loveleen; Mudimu, Edinah; Martin-Hughes, Rowan; Hamilton, Matt; Johnson, Leigh; ten Brink, Debra; Stover, John; Meyer-Rath, Gesine; Kelly, Sherrie L; Jamieson, Lise; Cambiano, Valentina; Jahn, Andreas; et al.
Summary: Background: Voluntary medical male circumcision (VMMC) has been a recommended HIV prevention strategy in sub-Saharan Africa since 2007, particularly in countries with high HIV prevalence. However, given the scale-up of antiretroviral therapy programmes, it is not clear whether VMMC still represents a cost-effective use of scarce HIV programme resources. Methods: Using five existing well described HIV mathematical models, we compared continuation of VMMC for 5 years in men aged 15 years and older to no further VMMC in South Africa, Malawi, and Zimbabwe and across a range of setting scenarios in sub-Saharan Africa. Outputs were based on a 50-year time horizon, VMMC cost was assumed to be US90, and a cost-effectiveness threshold of US500 was used. Findings: In South Africa and Malawi, the continuation of VMMC for 5 years resulted in cost savings and health benefits (infections and disability-adjusted life-years averted) according to all models. Of the two models modelling Zimbabwe, the continuation of VMMC for 5 years resulted in cost savings and health benefits by one model but was not as cost-effective according to the other model. Continuation of VMMC was cost-effective in 68% of setting scenarios across sub-Saharan Africa. VMMC was more likely to be cost-effective in modelled settings with higher HIV incidence; VMMC was cost-effective in 62% of settings with HIV incidence of less than 0·1 per 100 person-years in men aged 15–49 years, increasing to 95% with HIV incidence greater than 1·0 per 100 person-years. Interpretation: VMMC remains a cost-effective, often cost-saving, prevention intervention in sub-Saharan Africa for at least the next 5 years. Funding: Bill & Melinda Gates Foundation for the HIV Modelling Consortium.